Improving Medication Adherence In Hypertensive Patients: A Scoping Review - Simão Alves Pinho (2021)
In recent years, interest in medication adherence has greatly increased. Adherence has been particularly well studied in the context of arterial hypertension treatment. Numerous interventions have addressed this issue, however, the effort to improve adherence has been often frustrating and frequently disorganized. The aim of present study was to perform a scoping review of medication adherence interventions in hypertensive patients, so that a clear overview was achieved. Moreover, an evidence-based categorization of interventions was developed. The review was performed according to the PRISMA-ScR statement. MEDLINE and Web of Science were searched, and studies published from database inception until August 17, 2020 were included. A total of 2994 non-duplicate studies were retrieved. After screening and eligibility phases, a total of 45 articles were included. Studies were analyzed regarding their design, participant characteristics and management of adherence strategies employed. Furthermore, medication adherence and blood pressure outcomes, as well as adherence measuring tools were evaluated. Each study's intervention was then categorized using a novel evidence-based system of categorization, derived from the conceptual clustering framework used in machine learning. This work is an important step in pushing for better informed and more efficient future research efforts, both by providing an overview of the research field and by creating a new, evidence-based intervention categorization tool. It also provides valuable information to clinicians about medication adherence to antihypertensive therapy.